The Relationship of Transformational Leadership Style of Principals and Participation of Teachers in MGMP with Mathematics Teachers’ Performance - Sitisyarah, Kania; Aisyah, Aisyah (Jurnal Dosen Universitas PGRI Palembang)
AbstractThis study aimed at finding out (1) the relationship between the principals? transformational leadership style and the Mathematics teachers? performance; (2) relationship between teachers? participation in MGMP and Mathematics teachers? performance; and (3) the joint relationship between the principals? transformational leadership style and the teachers? participation in MGMP on the performance of Mathematics teachers in Palembang. This research was quantitative by using survey method. This research was conducted at the State Secondary School in Palembang with 73 Mathematics teachers. Data were collected by using questionnaires and documentation. The validity test applied on construction and content, while reliability tests used Cronbach?s Alpha. The data were analyzed by using t-test and F-test techniques. The results showed that (1) there was a positive and significant relationship between the principals? transformational leadership style and the Mathematics teacher's performance in with a correlation score 0.432 or a moderate positive relationship; (2) there is significant positive relationship between teachers? participation in MGMP and the performance of Mathematics teachers with a correlation score 0.420 or a moderate positive relationship; and (3) there was a joint relationship between the principals? transformational leadership style and the teachers? participation in MGMP with the performance of Mathematics teachers with a correlation score 0.488 or a moderate positive relationship with a percentage of relations of 23.8% while 76 2% is determined by other factors not mentioned in this study.KEYWORDS: Transformational Leadership Style; Teachers? Participation in MGMP; Mathematics Teachers? Performance